The Maher Cup. ([New South Wales] : Neil Pollock, 2013)
Life and football in the period from the 1920s to the 1960s in Tumut, Gundagai, Cootamundra, Young, Harden-Murrumburrah, Junee, Temora, Barmedman, West Wyalong, Cowra, Grenfell and Boorowa.
Title from title screen (viewed on 18 May 2017)
Mode of access: Available Online. Address as at 30/05/2017
Selected for archiving
Keywords: Rugby League football players -- New South Wales; Rugby League football -- Tournaments -- Australia; Rugby League football -- New South Wales -- History; Australian